1991
DOI: 10.1093/ajcn/54.3.509
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle density: effects of obesity and non-insulin-dependent diabetes mellitus

Abstract: Obesity is associated with increased lean mass but its effects on lean-tissue density are less clear. To examine the effects of obesity and non-insulin-dependent diabetes mellitus (NIDDM) on lean-tissue composition and density, cross-sectional computed tomography (CT) scans of the midthigh were obtained in 20 men of various weights. Obesity was associated with increases in thigh-adipose (r = 0.75) and lean-tissue volumes (r = 0.52) and with reduced density of lean tissue (r = -0.73). The increased lean tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
140
2
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(154 citation statements)
references
References 12 publications
9
140
2
3
Order By: Relevance
“…Similar negative association has been found between CT-evaluated muscle density measured in the mid thigh and BMI [31]. On the other hand, no association has been found between fat deposits in the back muscles, evaluated by MRI, and weight [32,46].…”
Section: Discussionsupporting
confidence: 71%
“…Similar negative association has been found between CT-evaluated muscle density measured in the mid thigh and BMI [31]. On the other hand, no association has been found between fat deposits in the back muscles, evaluated by MRI, and weight [32,46].…”
Section: Discussionsupporting
confidence: 71%
“…At a further increase in FMI, the SM increases underproportionately when compared with connective tissue (for example, FFM of AT). This was shown by Kelley et al, 35 who found a decreased density of lean tissue induced by a high proportion of connective tissue in the area of the muscle in obese subjects. A higher proportion of connective tissue alters the quality of FFM, which can lead to functional disability and mobility limitations.…”
Section: Discussionmentioning
confidence: 54%
“…Mid-thigh skeletal muscle area was compartmentalized into a low-density muscle area (0 to þ 34 HU) and a normal-density muscle area ( þ 35 to þ 100 HU). 10 Skeletal muscle attenuation was determined by measuring the mean value of all pixels within the range of 0 to þ 100 HU. In addition, as a valid tool for measuring the fat content of the liver, we determined liver attenuation as the average measurement from three regions of interest (one from each hepatic lobe) in the cross-sectional image at the T11-12 intervertebral disc space.…”
Section: Computed Tomography Imagingmentioning
confidence: 99%